The role of iGeneration and Silver generation in shaping sustainable food markets: a cross-generational analysis in Slovakia - Horská, Elena; Janšto, Erik; Šedík, Peter (Frontiers in Sustainable Food Systems, 2023)
The rising global phenomenon of sustainable consumption in the food market is progressively influencing a significant number of consumers on a worldwide scale. The main goal of this study was to analyze consumer attitudes toward selected sustainability issues (organic aspects, animal welfare, waste management, etc.) as well as marketing communication in the food market among two generations. Primary data were acquired by implementing an online questionnaire. In total, 950 respondents participated in the survey. The results showed that the iGeneration (iGen; 18–25 years) has a higher tendency than the Silver generation (58–76 years) to support sustainability issues such as recyclable packaging, organic production, and animal welfare, as well as to read the information regarding the product nutrition and composition. The Silver generation is more inclined toward Slovak origin and traditional Slovak dishes, and they consider television and the press as the main source of information. The results provide valuable insights for agrifood companies in developing consumer-driven marketing strategies. The main limitation is related to the application of self-reported measures. Future research may include cross-cultural studies and could be extended by incorporating other sustainable and environmental aspects.